The effect of horizontal resolution on simulation quality in the Community Atmospheric Model, CAM5.1. (5th November 2014) - Wehner, Michael F.; Reed, Kevin A.; Li, Fuyu; Prabhat; Bacmeister, Julio; Chen, Cheng‐Ta; Paciorek, Christopher; Gleckler, Peter J.; Sperber, Kenneth R.; Collins, William D.; Gettelman, Andrew; Jablonowski, Christiane
Abstract We present an analysis of version 5.1 of the Community Atmospheric Model (CAM5.1) at a high horizontal resolution. Intercomparison of this global model at approximately 0.25°, 1°, and 2° is presented for extreme daily precipitation as well as for a suite of seasonal mean fields. In general, extreme precipitation amounts are larger in high resolution than in lower‐resolution configurations. In many but not all locations and/or seasons, extreme daily precipitation rates in the high‐resolution configuration are higher and more realistic. The high‐resolution configuration produces tropical cyclones up to category 5 on the Saffir‐Simpson scale and a comparison to observations reveals both realistic and unrealistic model behavior. In the absence of extensive model tuning at high resolution, simulation of many of the mean fields analyzed in this study is degraded compared to the tuned lower‐resolution public released version of the model.